Application of Hardening State Parameter Constitutive Model for Prediction of Overconsolidated Soft Clay Behavior Due to Embankment Loading - Nikola Obradović; Sanja Jocković; Mirjana Vukićević (Applied Sciences, 2023)
This paper investigates the possibility of the application of the HArdening State Parameter (HASP) constitutive model for numerical modelling of overconsolidated soft clay under embankment loading. The HASP constitutive model is a critical state soil model with a combined hardening rule that uses a state parameter to determine the dilatancy of overconsolidated clay. The model overcomes some shortcomings of the Modified Cam Clay (MCC) model in the prediction of overconsolidated clay’s behavior, while preserving the simplicity and the same set of five parameters. The HASP model was implemented in finite element software. In order to verify the applicability of the model in predicting the behavior of soft overconsolidated clay due to embankment loading, two examples reported in the literature are analyzed. The numerical predictions of the HASP model are compared with the field measurements of ground settlements and pore water pressures, and with the MCC model’s predictions. The results indicate that the HASP model predicts the development of the settlements of the overconsolidated soft clay deposits with a high accuracy from an engineering point of view. There are certain deviations from the field measurements in predicting the pore pressure development, which is often observed for other models as well. For the embankment settlement assessment, as important serviceability issue, the HASP model has an advantage over more complex models that require a large number of parameters. Since the parameters of the HASP model are obtained from standard laboratory tests, it can be easily applied for routine geotechnical analyses.